Pertumbuhan dan Produksi Padi Sawah dan Gogo dengan Pemberian Pupuk Hayati Berbasis Bakteri Pemacu Tumbuh di Tanah Masam - Arie Aryanto; . Triadiati; . Sugiyanta (Jurnal Ilmu Pertanian Indonesia, 2015)
Biofertilizer is a substance which contains microorganism and promotes plant growth by increasing the soil nutrient availability. The aim of this study was to analyze the growth and production of lowland and upland rice by using the biofertilizer in acid soils. Seven isolates of bacteria were used as biofertilizer, i.e. Bacillus sp., two strains of Pseudomonas sp., two strains of Azospirillum sp., and two strains of Azotobacter sp.. The treatments of this study were without fertilization, compost, 100% NPK, compost enriched with 7 isolates, compost enriched with 7 isolates + 50% NPK, compost enriched with 4 isolates, and compost enriched with 4 isolates + 50% NPK. The results showed that biofertilizer in compost improved nutrient content in acid soil, and increased rice growth and production as well. Compost enriched with 7 isolates 50% NPK showed the highest rice yield production both in the lowland and upland rice. The biofertilizer could reduced 50% utilization NPK fertilizer dosage in the first growing season.